2018
DOI: 10.1186/s12944-018-0817-2
|View full text |Cite
|
Sign up to set email alerts
|

Blood lipid profile and body composition in a pediatric population with different levels of physical activity

Abstract: BackgroundAssociations between physical activity and lipid/lipoprotein levels and body composition among pediatric populations are not completely consistent in the literature. Accordingly, the aim of this study was to analyze lipid and lipoprotein profiles and body composition among children and adolescents differentiated according to their level of physical activity.MethodsThe study sample consisted of 69 participants that ranged from 6 to 17 years of age. Objective measures of physical activity were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
2
12
0
2
Order By: Relevance
“…Controversial data has been reported regarding the association between PA and lipid profile in a young population [55][56][57][58]. In agreement with previous studies [59,60], we found a lipid profile marker which consisted of lower LDL levels and higher HDL concentrations in Group C as compared with Group A, whereas TG levels were unmodified among groups.…”
Section: Discussionsupporting
confidence: 90%
“…Controversial data has been reported regarding the association between PA and lipid profile in a young population [55][56][57][58]. In agreement with previous studies [59,60], we found a lipid profile marker which consisted of lower LDL levels and higher HDL concentrations in Group C as compared with Group A, whereas TG levels were unmodified among groups.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, this study is the first to investigate the association of the number of breaks taken during SB, measured objectively by a device, and serum lipid profiles in a healthy middle-aged female population. Previous studies have focused on PA and SB in child [ 26 , 27 ], youth [ 28 ] or adult populations with certain physiological states or illnesses [ 29 31 ] or adults with different types of professions [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the rst to investigate the association of the number of breaks taken during SB, measured objectively by a device, and serum lipid pro les in a healthy middle-aged female population. Previous studies have focused on PA and SB in child ( 26,27), youth (28) or adult populations with certain physiological states or illnesses (29)(30)(31) or adults with different types of professions. (32,33) The quartile that had highest number of breaks per day had 0.11 mmol/l higher concentration of HDL and 0.10 mmol/l lower concentration of triglycerides compared to the quartile with lowest number of breaks in the adjusted model.…”
Section: Discussionmentioning
confidence: 99%